2015
DOI: 10.12691/jfnr-3-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Extracting Mycocin Secreted by Yeast Isolated from Koumiss and Their Antibacterial Effect

Abstract: Koumiss is a common fermented mare's milk with beneficial therapeutic effects on cardiovascular disease, tuberculosis, and diarrhea. The mare's milk is fermented by lactic acid bacteria (LAB) and yeasts. Although information about LAB from Koumiss is comprehensive, there is limited knowledge about yeasts from Koumiss and their effects. The purpose of this study was to screen and extract mycocin secreted by yeast isolated from Koumiss and test their antibacterial effect against pathogenic Escherichia coli, The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…41,42 Banjara et al (2016) 41 observed the production of mycocins by DH strains which were able to inhibit Candida albicans and C. tropicalis yeasts, especially under pH conditions from 4.5 to 5.5 and temperatures from 25°C to 30°C. 41 In addition, Chen et al (2015) 43 studied the production of mycocins by KM at pH 2 and 8, and the inhibitory effect on Escherichia coli was mainly observed in a temperature range from 25°C to 45°C. 43 This suggests that KM and DH could also produce mycocins as a survival mechanism and predominate in the environment.…”
Section: Whey Fermentation Under Monoculture Modementioning
confidence: 99%
“…41,42 Banjara et al (2016) 41 observed the production of mycocins by DH strains which were able to inhibit Candida albicans and C. tropicalis yeasts, especially under pH conditions from 4.5 to 5.5 and temperatures from 25°C to 30°C. 41 In addition, Chen et al (2015) 43 studied the production of mycocins by KM at pH 2 and 8, and the inhibitory effect on Escherichia coli was mainly observed in a temperature range from 25°C to 45°C. 43 This suggests that KM and DH could also produce mycocins as a survival mechanism and predominate in the environment.…”
Section: Whey Fermentation Under Monoculture Modementioning
confidence: 99%
“…Moreover, Hatoum et al [ 71 ] characterized anti-listerial hydrophobic peptides, extracted from four dairy yeast cultures identified as D. hansenii , Pichia fermentans , Candida tropicalis and Wickerhamomyces anomalus , which induced leakage in bacterial cells and ultimately caused bacterial lysis. More recently, Chen and co-workers [ 72 ] isolated two strains of Kluyveromyces marxianus producing mycocins from Koumiss in Inner Mongolia and demonstrated that the two crude extracts were effective at preventing Escherichia coli disease in mice. Finally, a very recent study, aimed at evaluating some probiotic properties of the P. pastoris strain X-33 wild-type, demonstrated the growth inhibition of Salmonella typhimurium in vitro and the reduction of bacterial adhesion to the human colorectal cancer HCT-116 cells [ 73 ].…”
Section: Antagonistic Mechanisms Of Yeastmentioning
confidence: 99%
“…This killer toxin are secondary metabolites (enzymes), of a protein or glycoprotein nature with antibiotic activity, as they cause disturbance in the cell wall of the pathogen and cause deleterious effects (Comitini et al, 2004). Other studies have identified the same potential in yeasts of the genera Debaryomyces, Pichia, Kluyveromyces, Wickerhamomyces, Williopsis and Zygosaccharomyces among others (Ceugniez et al, 2015;Chen et al, 2015;França et al, 2015;Hatoum et al, 2012;Passoth et al, 2011;Seddik et al, 2016).…”
Section: Introductionmentioning
confidence: 99%